Dynamic multi-omics and mechanistic modeling approach uncovers novel mechanisms of kidney fibrosis progression - Tüchler, Nadine; Burtscher, Mira Lea; Garrido-Rodriguez, Martin; Khan, Muzamil Majid; Türei, Dénes; Tischer, Christian; Kaspar, Sarah; Schwarz, Jennifer Jasmin; Stein, Frank; Rettel, Mandy; Kramann, Rafael; Savitski, Mikhail M; et al. (Molecular systems biology, 2025)
Kidney fibrosis, characterized by excessive extracellular matrix deposition, is a progressive disease that, despite affecting 10% of the population, lacks specific treatments and suitable biomarkers. This study presents a comprehensive, time-resolved multi-omics analysis of kidney fibrosis using an in vitro model system based on human kidney PDGFRβ+ mesenchymal cells aimed at unraveling disease mechanisms. Using transcriptomics, proteomics, phosphoproteomics, and secretomics, we quantified over 14,000 biomolecules across seven time points following TGF-β stimulation. This revealed distinct temporal patterns in the expression and activity of known and potential kidney fibrosis markers and modulators. Data integration resulted in time-resolved multi-omic network models which allowed us to propose mechanisms related to fibrosis progression through early transcriptional reprogramming. Using siRNA knockdowns and phenotypic assays, we validated predictions and regulatory mechanisms underlying kidney fibrosis. In particular, we show that several early-activated transcription factors, including FLI1 and E2F1, act as negative regulators of collagen deposition and propose underlying molecular mechanisms. This work advances our understanding of the pathogenesis of kidney fibrosis and provides a resource to be further leveraged by the community.